THE SUSTAINABLE DEVELOPMENT OF THAI BOXING FOR TOURISM - Chaichana Teerasukittima (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Today our government tries to make revenue from mixture between tourism and Muay Thai. Namely, it was found that Thai boxing camps were opened more than 8,000 camps throughout the United States and European counties as well. However, only a limited study has examined the way to improve Thai boxing for tourism; therefore, the major purpose of this research is to study how to sustainably develop Muay Thai industry for making revenue to Thailand (Bangkok and surrounding areas of Thailand as a case study). The result of this study will be used as guideline in improving the sport tourism of government agency like Tourism Authority of Thailand, Sport Authority of Thailand in the future.